Traditional knowledge of wild and semi-wild edible plants used in Bali (Indonesia) to maintain biological and cultural diversity. (2nd September 2016) - Sujarwo, W.; Arinasa, I. B. K.; Caneva, G.; Guarrera, P. M.
Abstract : We report the first ethnobotanical study of wild and semi-wild food plants used by the inhabitants of the villages of Bali. Considering the urgent need to avoid the loss of this traditional knowledge, 50 informants from 13 " Bali Aga " villages across four districts were selected for our field investigation. Ethnobotanical data were collected through different interview methods (direct observation, semi-structured interviews, key informant interviews, individual discussions, focus-group discussions, and questionnaires). The 86 recorded species belonging to 41 families and 68 genera, including angiosperms (82) and pteridophytes (4), are categorized as wild (33) and semi-wild (53), of which 63.64% are native to Malesian, Indian, and Indochinese. Wild and semi-wild edible plants play an important role in providing the Balinese with various essential nutrients. Fourteen species (16.28%) are also used medicinally. In recent years, with the growth of the tourist industry, the wild habitats of edible plants have been severely impacted. Traditional knowledge related to wild and semi-wild edible plants is also endangered. Therefore, the management of these resources and the preservation of biodiversity along with indigenous knowledge are of primary importance.